Dysfunction of endoscopic third ventriculostomy in children - Luciano Lopes Furlanetti; Marcelo Volpon Santos; Ricardo Santos de Oliveira; Matheus Fernando Manzolli Ballestero (Brazilian Society for Pediatric Neurosurgery, 2019)
Introduction: Neuroendoscopy is particularly useful as an adjunct in the treatment of hydrocephalus. CSF physiology differs among neonates, children and adults leading to different and conflicting results in the treatment of hydrocephalus using neuroendoscopy. The aim of our study was to review the literature regarding to analyze predictive clinical and imaging models available and discuss specific aspects of the endoscopic approach to hydrocephalus in infants Methods: Review of the medical literature to analyze predictive clinical and imaging models available and discuss specific aspects of the endoscopic approach to hydrocephalus children. Data of our series of ETV were analyzed. The patients were categorized in 3 groups: Group A (< 6 months of age), Group B (from 6 months to 1 year-old) and group C ( >1 year-old). Results: Group A - 12 patients , group B - 17 patients and group C - 85 patients. The etiology of hydrocephalus was tumors in 33 (29 %), aqueduct stenosis in 33 (29 %), cerebral malformations in 24 (21 %). The ETVSS in the low, moderate and high ETVSS groups was respectively 40%, 70.9% and 92.6%, the actual success rate: 58%, 65% and 86%. The complication rates in groups A, B and C were 33 %, 24 %, and 8 %, respectively (p=0.022). Conclusion: Endoscopic third ventriculostomy provides very good results for a number of indications in children. Every effort should be made to optimize the selection of surgical candidates on the basis of their clinical features.